2021
DOI: 10.1002/jgh3.12531
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin inhibitors in steroid and anti‐TNF‐alpha refractory immune checkpoint inhibitor colitis

Abstract: Background and Aim: Immune checkpoint inhibitor (ICI) colitis is an increasingly common problem encountered as the use of checkpoint inhibitors (CPIs) grows in the management of cancers. Corticosteroids and tumour necrosis factor (TNF)-alpha inhibitors are widely recommended in the management of ICI colitis; however, the experience is limited when patients are refractory. Different authors have reported success with vedolizumab, mycophenolate, and cyclosporine. This case series describes our experience with ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Overall, calcineurin inhibitors were well tolerated, hence it was concluded that in patients with refractoriness to corticosteroids and infliximab treatment, calcineurin inhibitor treatment should be considered and, with close monitoring, adverse effects caused by calcineurin inhibitors including acute kidney injury can be addressed or avoided promptly. [ 1 ]…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, calcineurin inhibitors were well tolerated, hence it was concluded that in patients with refractoriness to corticosteroids and infliximab treatment, calcineurin inhibitor treatment should be considered and, with close monitoring, adverse effects caused by calcineurin inhibitors including acute kidney injury can be addressed or avoided promptly. [ 1 ]…”
Section: Literature Reviewmentioning
confidence: 99%
“…[112,114,115]. Due to the irAEs' complexity and unclear pathogenesis, other immunotherapie currently under evaluation as potential alternatives to VDZ and IFX, such as calcine inhibitors [177], anti-IL-23 and anti-IL-12 blockade [178] and Janus kinase (JAK) inhibi such as tofacitinib [179].…”
Section: Managementmentioning
confidence: 99%
“… 109 Selective intestinal activity could assume particular relevance in limiting systemic immunosuppression without altering the antitumor response to therapy and without enhancing tumor progression in patients with lymph node involvement. 110 However, it should be used with caution in patients with gastrointestinal tract tumors or gastrointestinal tract infection. In a retrospective study, Abu-Sbeih et al reported a lower relapse rate in patients receiving vedolizumab compared with infliximab.…”
Section: Therapeutic Approachesmentioning
confidence: 99%